Participation, learning, and equity in education: Can we have it all? - Delavallade, Clara; Griffith, Alan; Shukla, Gaurav; Thornton, Rebecca (International Food Policy Research Institute, 2017)
The United Nations Sustainable Development Goals have set a triple educational objective: improving access to, quality of, and gender equity in education. This study is the first to document the effectiveness of policies targeting all these objectives simultaneously. We examine the impact of a multifaceted educational program—delivered to 230 randomly selected primary schools in rural India—on students’ participation and performance. We also study the heterogeneity of this impact across gender and initial school performance, and its sustainability over two years. Although the program specifically targeted outof-school girls for enrollment, the learning component of the program targeted boys and girls equally. We find that the program reduced gender gaps in school retention and improved learning during the first year of implementation. However, targeting different educational goals (access, quality, and equity) did not yield sustained effects on school attendance or learning, nor did it bridge gender inequalities in school performance over the two-year period.